Optimalisasi Pembelajaran Piano dengan Pendekatan Deep Learning - Lingga Ramafisela (Universitas Negeri Medan, 2025)
Learning is an activity aimed at acquiring knowledge and skills useful in life. Piano lessons conducted in the Music Education study program, Faculty of Performing Arts, ISI Yogyakarta, are part of formal education. Current piano lessons must be optimized with a different approach than the previous teacher-centered approach. A deep learning approach can be used to help students understand the fundamentals of piano. The deep learning approach has three main elements: meaningful learning, mindful learning, and joyful learning, which can be used to overcome the difficulties faced by students. This research used a qualitative method based on data obtained in the field, namely in the piano instrument study class in the Music Education study program, Faculty of Performing Arts, ISI Yogyakarta. The research approach used was a case study. Data collection techniques were conducted through literature/document studies, observation, and interviews. The data analysis process consisted of data reduction, data presentation, and drawing conclusions based on the data obtained during the fieldwork.